Polypropylene composition
By adjusting the ratio and composition of propylene homopolymer and propylene-ethylene copolymer, and by employing specific Ziegler-Natta catalysts and polymerization processes, the shortcomings of polypropylene compositions in terms of processability, stiffness, and transparency have been overcome, resulting in high-performance polypropylene compositions suitable for injection molding and thermoforming products.
Patent Information
- Application Number
- CN202480052422.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-12
- Filing Date
- 2024-08-26
- Publication Date
- 2026-03-17
AI Technical Summary
Existing polypropylene compositions are inadequate in terms of processability, rigidity, and transparency, making it difficult to meet the requirements of injection-molded and thermoformed products.
By adjusting the ratio and composition of propylene homopolymer and propylene-ethylene copolymer, and using specific Ziegler-Natta catalysts and polymerization processes, polypropylene compositions are prepared in gas-phase and bulk polymerization to ensure high melt flow rates and intrinsic viscosity, and appropriate nucleating agents are added to improve performance.
A polypropylene composition with excellent mechanical properties, good haze and processability was obtained, which is suitable for injection molding and thermoforming products, especially containers.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This disclosure relates to a polypropylene copolymer composition having a combination of improved processability, stiffness, and transparency. These compositions can be used to produce molded articles, particularly injection-molded articles, or thermoformed articles such as containers. Background Technology
[0002] Injection-molded parts, such as food packaging and plastic cups, impose specific requirements on the polymer materials used to produce these products.
[0003] Polypropylene-based polymers have many properties that make them suitable for applications such as molded articles, pipes, fittings, and foams.
[0004] Typically, high-rigidity polypropylene products are based on high molecular weight materials, which are usually nucleated by adding nucleating agents, that is, crystallization begins at higher temperatures and at a high rate.
[0005] WO 2018 / 104092 relates to a polypropylene composition comprising:
[0006] A) 50% to 90% by weight of propylene homopolymers having an MFR L of 0.5 g / 10 min to 200 g / 10 min;
[0007] B) A copolymer of propylene and ethylene from 10% to 50% by weight, the copolymer having from 30.0% to 70.0% by weight ethylene-derived units;
[0008] The total amount of components A) and B) is 100;
[0009] The composition has the following characteristics:
[0010] i) The intrinsic viscosity of the fractions soluble in xylene at 25°C, including fractions between 2.2 dl / g and 4.0 dl / g;
[0011] ii) MFR L (from 0.5 g / 10 min to 50 g / 10 min);
[0012] iii) Xylene soluble fractions ranging from 20% to 50% by weight.
[0013] It has been found that by fine-tuning polypropylene copolymer compositions containing propylene homopolymer and propylene ethylene homopolymer, copolymers with good mechanical properties and good haze can be obtained. Summary of the Invention
[0014] Therefore, this disclosure provides a polypropylene composition comprising:
[0015] A) A propylene homopolymer ranging from 65.5% to 82.5% by weight, having a fraction of more than 95.0% by weight that is insoluble in xylene at 25°C; and a melt flow rate (MFR) between 50.0 g / 10 min and 80.0 g / 10 min, measured according to ISO 1133 at 230°C and a load of 2.16 kg.
[0016] B) A propylene-ethylene copolymer from 17.5% to 34.5% by weight, wherein the propylene-ethylene copolymer has the property of passing through 13 CNMR measurements range from 38.2 wt% to 48.3 wt% of ethylene-derived units.
[0017] The polypropylene composition has the following characteristics:
[0018] i) Xylene-soluble fractions at 25°C ranging from 24.0% to 32.3% by weight;
[0019] ii) Through 13 C NMR measurements were performed on the ethylene-derived unit content in the fraction of xylene soluble at 25°C, ranging from 34.6 wt% to 42.0 wt%.
[0020] iii) Melt flow rate (MFR) measured according to ISO 1133 at 230°C and 2.16 kg load, including values between 12.0 g / 10 min and 38.0 g / 10 min;
[0021] iv) The intrinsic viscosity of this fraction in tetrahydronaphthalene, soluble in xylene at 25°C, measured at 135°C, ranges from 2.2 dl / g to 3.5 dl / g;
[0022] The sum of the quantities of A) and B) is 100 units of weight. Detailed Implementation
[0023] Therefore, this disclosure provides a polypropylene composition comprising:
[0024] A) a propylene homopolymer comprising 65.5% to 82.5% by weight, preferably 69.2% to 80.2% by weight, more preferably 71.0% to 78.0% by weight, having a fraction of greater than 95.0% by weight, preferably greater than 97.2% by weight, that is insoluble in xylene at 25°C; and a melt flow rate (MFR) measured according to ISO 1133 at 230°C and a load of 2.16 kg, comprising between 50.0 g / 10 min and 80.0 g / 10 min, preferably between 55.0 g / 10 min and 75.0 g / 10 min, more preferably between 60.0 g / 10 min and 70.0 g / 10 min;
[0025] B) A propylene-ethylene copolymer comprising, in an amount from 17.5 wt% to 34.5 wt%, preferably from 19.8 wt% to 30.8 wt%, and more preferably from 22.0 wt% to 29.0 wt%, of a propylene-ethylene copolymer having the properties of, through 13 The C NMR measurement range is from 38.2 wt% to 48.3 wt%, preferably from 40.6 wt% to 47.4 wt%, and more preferably from 42.5 wt% to 47.0 wt% of ethylene-derived unit content;
[0026] The polypropylene composition has the following characteristics:
[0027] i) A xylene-soluble fraction at 25°C ranging from 24.0 wt% to 32.3 wt%, preferably from 24.5 wt% to 30.5 wt%, and more preferably from 25.0 wt% to 29.0 wt%;
[0028] ii) Through 13 The range of C NMR measurements is from 34.6 wt% to 42.0 wt%, preferably from 35.2 wt% to 41.0 wt%, and more preferably from 36.5 wt% to 40.0 wt% of the content of the ethylene-derived unit in the fraction soluble in xylene at 25°C.
[0029] iii) The melt flow rate (MFR) measured according to ISO 1133 at 230°C and a load of 2.16 kg, comprising between 12.0 g / 10 min and 38.0 g / 10 min, preferably between 14.0 g / 10 min and 32.0 g / 10 min, and more preferably between 16.0 g / 10 min and 28.0 g / 10 min;
[0030] iv) The intrinsic viscosity of the fraction in tetrahydronaphthalene that is soluble in xylene at 25°C, measured at 135°C, is in the range of 2.2 dl / g to 3.5 dl / g, preferably from 2.4 dl / g to 3.2 dl / g, and more preferably from 2.6 dl / g to 3.0 dl / g.
[0031] The sum of the quantities of A) and B) is 100 units of weight.
[0032] For the purposes of this disclosure, the term "copolymer" refers to a polymer containing only two comonomers, such as propylene and ethylene.
[0033] The polypropylene compositions disclosed herein do not undergo chemical or physical viscous cracking, i.e., MFR is obtained through a polymerization process.
[0034] The polypropylene compositions according to this disclosure are preferably characterized by having one or more of the following properties:
[0035] a) The tensile modulus is between 1000 MPa and 700 MPa; preferably between 920 MPa and 750 MPa;
[0036] b) Charpy impact measured at 23°C is higher than 35.0 kJ / m. 2 Preferably higher than 40 kJ / m 2 More preferably higher than 43.0 kJ / m 2 The highest value is 80 kJ / m 2 ;
[0037] c) The elongation at break is greater than 300%, preferably greater than 380%, more preferably greater than 450%; the higher value is 1000%.
[0038] These characteristics, due to the specific polymerization process used and the specific Ziegler-Natta catalyst used in the polymerization, make the polypropylene compositions according to this disclosure particularly suitable for the production of molded articles, especially injection-molded or thermoformed articles. The polypropylene compositions of this disclosure are obtained by a polymerization process in two or more stages, wherein component A) is obtained in a first stage, and then component B) is obtained in a second stage in the presence of component A). Each stage can be carried out in a gas phase in one or more fluidized or mechanically stirred bed reactors, in a slurry phase using an inert hydrocarbon solvent as a diluent, or in bulk polymerization using a liquid monomer (e.g., propylene) as the reaction medium. Preferably, component B) is polymerized in a gas-phase process in the presence of component A).
[0039] Polymerization is typically carried out at temperatures ranging from 20°C to 120°C, preferably from 40°C to 80°C. When polymerization is carried out in the gas phase, the working pressure is typically between 0.5 MPa and 5 MPa, preferably between 1 MPa and 4 MPa. In bulk polymerization, the working pressure is typically between 1 MPa and 8 MPa, preferably between 1.5 MPa and 5 MPa. Hydrogen is typically used as a molecular weight regulator.
[0040] The polypropylene composition disclosed herein can be obtained by a method comprising: polymerizing propylene in a first stage (A); and copolymerizing propylene with ethylene in a second stage (B), wherein a solid catalyst component for polymerizing olefins is present in both stages, the solid catalyst component comprising magnesium halide and a titanium compound having at least a Ti-halogen bond and at least an electron donor of formula (I):
[0041]
[0042] (I)
[0043] Where R 1 and R 2 Independently, it is a C1-C5 alkyl group, where X is Si or C, and R is... 3 and R 4 The groups are independently selected from hydrogen, C1-C. 10 Hydrocarbon groups and halogens, provided that there are at least two R groups. 3 It's not hydrogen.
[0044] Preferably, R 1 and R 2 The same and selected from C1-C4 straight-chain or branched alkyl groups, and more preferably selected from methyl groups.
[0045] Preferably, R 4 The group is independently selected from hydrogen, C1-C4 straight-chain or branched alkyl groups, and halogens. More preferably, R 4 Only one or two groups in the group are C1-C4 straight-chain or branched alkyl groups or halogens. Preferred alkyl groups are methyl, isopropyl, or tert-butyl, while preferred halogens are Cl and F. All R... 4 A structure with hydrogen as a radical is also preferred.
[0046] When R 3 When it is a hydrocarbon group, it is preferably selected from C1-C4 straight-chain or branched alkyl groups, and more preferably from methyl groups.
[0047] When R 3 When the halogen is halogen, it is preferably selected from Cl and F. More preferably, the halogen is F.
[0048] According to a preferred embodiment, X is carbon, and R 3 It is hydrogen or preferably a C1-C4 straight-chain or branched alkyl group, more preferably a hydrocarbon group selected from methyl. Most preferably, one of the R groups is... 3 The structure is selected from hydrogen and the other two are selected from methyl groups.
[0049] Another preferred structure is one in which X is carbon, and R 3 It is hydrogen or preferably those structures selected from Cl and F, more preferably those selected from halogen groups of F. Most preferably, it is those in which R... 3 At least two of the structures are selected from F, and more preferably all of the R are selected from F. 3 Structures whose radical is F.
[0050] According to another preferred embodiment, X is Si, and R 3 It is hydrogen or preferably a C1-C4 straight-chain or branched alkyl group, more preferably a hydrocarbon group selected from methyl or ethyl. Most preferably, all R... 3 The group is selected from the structure of methyl.
[0051] Preferably, the electron donor of formula (I) is 2-cyclohexyl-2-isopentyl-1,3-dimethoxypropane; or 2-cyclohexyl-2-(3,3,3-trifluoro-n-propyl)-1,3-dimethoxypropane.
[0052] By using the described catalyst components, propylene-ethylene copolymers with the specific properties reported herein can be obtained.
[0053] The solid catalyst component can be prepared by several methods.
[0054] According to one method, this solid catalyst component can be prepared by reacting the following: Ti(OR) q- y X yThe adduct is a titanium compound (where q is the valence of titanium and y is a number between 1 and q), preferably TiCl4, with magnesium chloride derived from the formula MgCl2•pROH, where p is a number between 0.1 and 6, preferably 2 to 3.5, and R is a hydrocarbon group having 1 to 18 carbon atoms. The adduct can be suitably prepared in spherical form by mixing an alcohol and magnesium chloride under stirring at the melting temperature of the adduct (100°C to 130°C). The adduct is then mixed with an inert hydrocarbon that is immiscible with the adduct to produce an emulsion, which is rapidly quenched, causing the adduct to solidify in the form of spherical particles. Examples of spherical adducts prepared according to this procedure are described in USP 4,399,054 and USP 4,469,648. The adduct thus obtained can react directly with the Ti compound, or it can be pre-treated with thermally controlled alcoholization (80°C to 130°C) to obtain an adduct in which the molar number of alcohol is typically less than 3, preferably between 0.1 and 2.5. The reaction with the Ti compound can be carried out by suspending the adduct (alcoholized or as is) in cold TiCl4 (typically about 0°C); heating the mixture to 80°C to 130°C and holding it at that temperature for 0.5 to 2 hours. The treatment with TiCl4 can be performed once or multiple times. Electron donor compounds can be added in the desired proportions during the TiCl4 treatment.
[0055] Suitable external electron donor compounds include silicon compounds, ethers, esters, amines, heterocyclic compounds, and especially 2,2,6,6-tetramethylpiperidine and ketones.
[0056] A preferred type of external donor compound is formula (R6). a (R7) b Si(OR8) c The silicon compound wherein a and b are integers from 0 to 2, c is an integer from 1 to 4, and the sum of (a+b+c) is 4; R6, R7, and R8 are alkyl, cycloalkyl, or aryl groups having 1 to 18 carbon atoms, optionally containing heteroatoms. Particularly preferred are silicon compounds wherein a is 1, b is 1, c is 2, at least one of R6 and R7 is selected from branched alkyl, cycloalkyl, or aryl groups having 3 to 10 carbon atoms, optionally containing heteroatoms, and R8 is C1-C6. 10Alkyl groups, particularly methyl groups. Examples of such preferred silicon compounds are methylcyclohexyldimethoxysilane (C donor), diphenyldimethoxysilane, methyl-tert-butyldimethoxysilane, dicyclopentyldimethoxysilane (D donor), diisopropyldimethoxysilane, (2-ethylpiperidinyl)tert-butyldimethoxysilane, (2-ethylpiperidinyl)tert-hexyldimethoxysilane, (3,3,3-trifluoro-n-propyl)(2-ethylpiperidinyl)dimethoxysilane, and methyl(3,3,3-trifluoro-n-propyl)dimethoxysilane. Furthermore, silicon compounds in which a is 0, c is 3, R7 is optionally a branched alkyl or cycloalkyl group containing a heteroatom, and R8 is methyl. Examples of such preferred silicon compounds are cyclohexyltrimethoxysilane, tert-butyltrimethoxysilane, and tert-hexyltrimethoxysilane.
[0057] The amount of electron donor compound (iii) is such that the weight ratio between the organoaluminum compound and the electron donor compound (iii) is from 2.5 to 500, preferably from 3 to 300, and more preferably from 3.5 to 100.
[0058] The polymerization process can be carried out using known techniques, such as slurry polymerization using inert hydrocarbon solvents as diluents, or bulk polymerization using liquid monomers (e.g., propylene) as the reaction medium. Alternatively, the polymerization process can be carried out in the gas phase in one or more fluidized bed or mechanically stirred bed reactors.
[0059] Polymerization is typically carried out at temperatures ranging from 20°C to 120°C, preferably from 40°C to 80°C. When polymerization is carried out in the gas phase, the working pressure is typically between 0.5 MPa and 5 MPa, preferably between 1 MPa and 4 MPa. In bulk polymerization, the working pressure is typically between 1 MPa and 8 MPa, preferably between 1.5 MPa and 5 MPa. Hydrogen is typically used as a molecular weight regulator.
[0060] The polypropylene compositions disclosed herein may contain additives commonly used in the art, such as antioxidants, processing stabilizers, slip agents, antistatic agents, anti-caking agents, anti-fogging agents, and nucleating agents.
[0061] The following embodiments are given for illustrative purposes and not for limiting the scope of this disclosure:
[0062] Example
[0063] Xylene-soluble (XS) fraction at 25°C
[0064] The xylene soluble content at 25°C has been determined according to ISO 16 152.
[0065] Intrinsic viscosity (IV)
[0066] The sample was dissolved in tetrahydronaphthalene at 135°C and then poured into a capillary viscometer. The viscometer tube (Ubbelohde type) was surrounded by a cylindrical glass jacket; this setup allows for temperature control using a circulating thermostatic liquid. The downward passage of the meniscus was timed by a photoelectric device.
[0067] The meniscus is activated by a counter with a quartz crystal oscillator as it passes the upper lamp. When it passes the lower lamp, the meniscus stops the counter, and the outflow time is recorded: this is converted to an intrinsic viscosity value using the Huggins equation (Huggins, ML, *Journal of the American Chemical Society*, 1942, 64, 2716), provided that the flow time of the pure solvent is known under the same experimental conditions (same viscometer and same temperature). [η] is determined using a single polymer solution.
[0068] Charpy impact test
[0069] Charpy impact test according to ISO 179-1eA, e ISO 1873-2
[0070] tensile modulus
[0071] Measure the tensile modulus on injection-molded samples according to ISO 527-2 and ISO 1873-2
[0072] oligomer content
[0073] The determination of oligomer content by solvent extraction involved treating a 5 g polypropylene sample with 10 ml of dichloromethane (CH2Cl2) in an ultrasonic bath at 25°C for 4 hours. A 1 ml extract solution was injected into a capillary column and analyzed using FID without filtration. For quantitative estimation of oligomer content, calibration based on an external standard method was applied. Specifically, a range of hydrocarbons (Cl2-C22-C28-C40) were used.
[0074] Melt flow rate (MIL)
[0075] The melt flow rate (MIL) of the polymer was determined according to ISO 1133 (230°C, 2.16 kg).
[0076] propylene / ethylene copolymer 13 C NMR
[0077] Acquired on a Bruker AV-600 spectrometer equipped with a cryoprobe. 13 C NMR spectroscopy, the spectrometer was operated at 120 °C in Fourier transform mode at 160.91 MHz.
[0078] S at 29.9 ppm ββ Carbon peaks (according to the nomenclature of "Monomer sequence distribution in ethylene-propylene rubber by 13C NMR. 3. Use of reaction probability mode" CJ Carman, RA Harrington, and CE Wilkes, Macromolecules, 1977, 10, 536) were used as internal references. Samples were dissolved at 120 °C in 1,1,2,2-tetrachloroethane-d2 at a concentration of 8 wt / v. Each spectrum was acquired with a 90° pulse, with a 15-second delay between the pulse and CPD to remove 1H-13C coupling. 512 transients were stored in 32K data points using a 9000 Hz spectral window.
[0079] The spectral assignment, triplet state distribution, and composition assessment were performed according to Kakugo (“Carbon-13 NMR determination of monomer sequence distribution in ethylene-propylene copolymers prepared with δ-titanium trichloride-diethylaluminum chloride”, M. Kakugo, Y. Naito, K. Mizunuma, and T. Miyatake, *Macromolecules*, 1982, 15, 1150) using the following equations:
[0080] PPP = 100 T ββ / S PPE = 100 T βδ / S EPE = 100 T δδ / S
[0081] PEP = 100 S ββ / S PEE= 100 S βδ / S EEE = 100 (0.25 S γδ +0.5 S δδ ) / S
[0082] S = T ββ + T βδ + T δδ + S ββ + S βδ + 0.25 Sγδ + 0.5 S δδ
[0083] The molar percentage of ethylene content is evaluated using the following equation:
[0084] E% mol = 100 * [PEP+PEE+EEE]
[0085] The weight percentage of ethylene content is evaluated using the following equation:
[0086]
[0087] Where P mol% is the molar percentage of propylene content, and MW E and MW P These are the molecular weights of ethylene and propylene, respectively.
[0088] The product of the reactivity ratios, r1r2, is calculated according to Carman (CJ Carman, RA Harrington, and CE Wilkes, *Macromolecules*, 1977; 10, 536):
[0089]
[0090] The stereoregularity of the propylene sequence was determined by PPP mmT. ββ (28.90 ppm to 29.65 ppm) and total T ββ The ratio of (29.80 ppm to 28.37 ppm) is calculated as mm content.
[0091] The ethylene content (C2) of component B is calculated using the following equation: C2tot = C2 b X2; where X2 is a fraction (ranging from 0 to 1) of component B present in composition X2.
[0092] Flexural modulus
[0093] The flexural modulus shall be measured in accordance with ISO 178, with supplementary conditions in accordance with ISO 1873-2.
[0094] Charpy impact test at 23°C
[0095] Charpy impact test is measured according to ISO 179-1eA, e ISO 1873-2.
[0096] Elongation at break
[0097] Elongation at break measured according to ISO 527-2 and ISO 1873-2
[0098] Heat distortion temperature (HDT)
[0099] Measured at 0.45 MPa according to ASTM D 648.
[0100] catalyst system
[0101] The catalyst system was produced according to the method described in PCT / EP2023 / 068696. The catalyst used in Example 1 is described in Example 15 of PCT / EP2023 / 068696. The catalyst used in Example 2 is described in Example 16 of PCT / EP2023 / 068696.
[0102] Propylene / ethylene copolymerization Examples 1 to 2
[0103] Prepolymerization treatment
[0104] Before introducing the solid catalyst components described above into the polymerization reactor, they were contacted with triethylaluminum (TEAL) and dicyclopentyldimethoxysilane (donor D) in the proportions reported in Table 1. The mixture was then prepolymerized at 20°C by keeping it suspended in liquid propylene for 5 minutes before being introduced into the polymerization reactor.
[0105] polymerization
[0106] The polymerization process is carried out in a continuous series of three reactors, each equipped with a device to transfer the product from one reactor to an adjacent one. The first two reactors are liquid-phase reactors, and the third reactor is a fluidized bed gas-phase reactor. Component (A) is prepared in the first and second reactors, which have the same polymerization parameters, while component (B) is prepared in the third reactor.
[0107] Hydrogen is used as a molecular weight regulator.
[0108] Continuous analysis of gas phases (propylene, ethylene, and hydrogen) using gas chromatography.
[0109] At the end of the operation, the powder is discharged and dried under a nitrogen stream.
[0110] The main polymerization conditions are reported in Table 1.
[0111] Table 1
[0112]
[0113] C3 propylene, C2 ethylene, H2 hydrogen
[0114] The polymers of Examples 1 and 2, as well as Comparative Example 3, have been characterized as reported in Table 2.
[0115] Table 2
[0116]
[0117] Comparative Example 3 is the commercial-grade SG702 sold by LyondellBasell.
[0118] Examples 1 and 2 show better Charpy ratio and elongation at break compared to Comparative Example 3.
Claims
1. A polypropylene composition comprising: A) from 65.5 wt% to 82.5 wt% of a propylene homopolymer having a fraction insoluble in xylene at 25°C of more than 95.0 wt%; and a melt flow rate MFR comprised between 50.0 g / 10 min and 80.0 g / 10 min measured according to ISO 1133 at 230°C and under a load of 2.16 kg; B) from 17.5 wt% to 34.5 wt% of a propylene ethylene copolymer having a melt flow rate MFR2.0 of from 0.5 to 2.0 g / 10 min, a density of from 905 to 915 kg / m3, and a content of ethylene derived units in the range from 40.6 wt% to 47.4 wt% as measured by13C NMR; 13 C a content of ethylene derived units in the range from 40.6 wt% to 47.4 wt% as measured by13C NMR; said polypropylene composition having: i) a fraction soluble in xylene at 25°C ranging from 24.0 wt% to 32.3 wt% measured according to ISO 16 152; ii) by 13 the ethylene derived unit content in said fraction soluble in xylene at 25°C in the range from 34.6 wt% to 42.0 wt%; iii) a melt flow rate MFR comprised between 14.0 g / 10 min and 38.0 g / 10 min measured according to ISO 1133 at 230°C and under a load of 2.16 kg; iv) an intrinsic viscosity of the fraction soluble in xylene at 25°C ranging from 2.2 dl / g to 3.5 dl / g measured in tetraline at 135°C; the sum of the amount of A) and the amount of B) being 100 wt%.
2. The polypropylene composition according to claim 1, wherein the polypropylene composition comprises from 69.2 wt% to 80.2 wt% of component A) and from 19.8 wt% to 30.8 wt% of component B).
3. The polypropylene composition according to any one of claims 1 to 2, wherein the fraction soluble in xylene at 25°C ranges from 24.5 wt% to 30.5 wt%.
4. The polypropylene composition according to any one of claims 1 to 3, wherein in component A) the melt flow rate MFR measured according to ISO 1133 at 230°C and under a load of 2.16 kg is comprised between 55.0 g / 10 min and 75.0 g / 10 min.
5. The polypropylene composition according to any one of claims 1 to 4, wherein the intrinsic viscosity of the fraction soluble in xylene at 25°C measured in tetraline at 135°C ranges from 2.4 dl / g to 3.2 dl / g.
6. The polypropylene composition according to any one of claims 1 to 5, wherein the ethylene derived units content in the fraction soluble in xylene at 25°C ranges from 35.2 wt% to 41.0 wt%.
7. The polypropylene composition according to any one of claims 1 to 6, wherein the ethylene derived units content in the fraction soluble in xylene at 25°C ranges from 36.5 wt% to 40.0 wt%.
8. The polypropylene composition according to any one of claims 1 to 7, wherein the intrinsic viscosity measured on the fraction soluble in xylene at 25°C ranges from 2.6 dl / g to 3.0 dl / g.
9. The polypropylene composition according to any one of claims 1 to 8, wherein the melt flow rate MFR measured according to ISO 1133 at 230 °C and a load of 2.16 kg is comprised between 14.0 g / 10 min and 32.0 g / 10 min.
10. The polypropylene composition according to any one of claims 1 to 9, wherein the polypropylene composition comprises from 71.0 wt% to 78.0 wt% of component A) and from 22.0 wt% to 29.0 wt% of component B).
11. The polypropylene composition according to any one of claims 1 to 10, obtainable by a process comprising polymerizing propylene in a first stage (A) and copolymerizing propylene with ethylene in a second stage (B), in both stages being present a solid catalyst component for the polymerization of olefins comprising a magnesium halide, a titanium compound having at least a Ti-halogen bond and at least an electron donor of formula (I): (I) wherein R 1 and R 2 are independently C1-C5 alkyl groups, X is Si or C, R 3 and R 4 groups are independently selected from hydrogen, C1-C 10 hydrocarbon groups and halogen, with the proviso that at least two R 3 are not hydrogen.
12. The polypropylene composition according to claim 11, wherein in the compound of formula (I) R 1 and R 2 are the same and are selected from C1-C4 linear or branched alkyl groups.
13. The polypropylene composition copolymer according to claim 11 or 12, wherein in the compound of formula (I), R 4 groups are independently selected from the group consisting of hydrogen, C1-C4 linear or branched alkyl groups and halogen.
14. The polypropylene composition according to claim 11 or 12, wherein in the compound of formula (I) R 3 is selected from a C1-C4 linear or branched alkyl group.
15. An injection molded article comprising the polypropylene composition according to claims 1 to 14.
Citation Information
Patent Citations
Heterophasic propylene copolymers
WO2018104092A1
